Uji Efektivitas E-Modul Laju Reaksi Berbasis Inquiry Terbimbing Terintegrasi Ayat-Ayat Al-Qur’an - Silvia, Bisminur; Iryani, Iryani (Universitas Negeri Padang, 2026)
The use of engaging and interactive electronic learning resources, such as e-modules, can enhance students' independence in understanding the learning content.. This research is designed to evaluate the impact of the reaction rate e-module that combines Guided Inquiry with verses from the Qur'an on the educational achievements of grade XI Phase F learners at SMA Pembangunan Laboratorium UNP. Information was gathered through pretests and posttests. The findings revealed that the experimental group achieved an average N-Gain of 0.73, categorized as high, with a t-value of 7.32, which is greater than the t-table value of 1.69, showing a notable difference compared to the control group. Therefore, the e-module based on Guided Inquiry, combined with Qur'anic verses, was deemed effective in enhancing students’ cognitive learning outcomes regarding reaction rate concepts.